1997
DOI: 10.1111/j.1365-2044.1997.198-az0333.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of co‐induction with midazolam upon recovery from propofol infusion anaesthesia

Abstract: We studied tracheal intubation conditions produced by the muscle relaxant, cisatracurium, following induction of anaesthesia with fentanyl (2 mg.kg ÿ 1) and thiopentone (6 mg.kg ÿ 1). Sixty patients were randomly assigned to receive cisatracurium in a single bolus dose of either 0.15 or 0.20 mg.kg ÿ 1. Tracheal intubation was commenced 120 s after injection of the relaxant. The mean (SD) time taken to achieve intubation was significantly shorter in the 0.20 mg.kg ÿ 1 group (137 (16) s) than the 0.15 mg.kg ÿ 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…We were unable to demonstrate any difference in adverse events such as coughing, laryngospasm or involuntary movements between groups. There is conflicting data in the literature with respect to time to discharge, which reflects differences in study design [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to demonstrate any difference in adverse events such as coughing, laryngospasm or involuntary movements between groups. There is conflicting data in the literature with respect to time to discharge, which reflects differences in study design [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…7 However, topical lidocaine can be unpleasant to taste and may produce upper airway obstruction, s Recovery from anesthesia can be delayed with midazolam co-induction. 9 The aim of our study was to determine whether the use of thiopental in combination with low dose atracurium provided LMA insertion conditions comparable with those after propofol.…”
mentioning
confidence: 99%
“…Djaiani and Ribes-Pastor [12] reported that the addition of midazolam (0.05 mg·kg Ϫ1 ) to propofol induction delayed the time of discharge from the hospital. In another study, Tighe and Warner [15] investigated the effect of midazolam-propofol coinduction on psychomotor recovery by using psychomotor tests. Coinduction with midazolam reduced psychomotor recovery in the immediate postoperative phase following propofol infusion anesthesia.…”
Section: Discussionmentioning
confidence: 99%